Characterization of CoQ10 biosynthesis in fibroblasts of patients with primary and secondary CoQ10 deficiency. Issue 1 (18th June 2013) - Buján, Nuria; Arias, Angela; Montero, Raquel; García‐Villoria, Judit; Lissens, Willy; Seneca, Sara; Espinós, Carmen; Navas, Plácido; De Meirleir, Linda; Artuch, Rafael; Briones, Paz; Ribes, Antonia
Abstract: Primary coenzyme Q10 (CoQ10 ) deficiencies are associated with mutations in genes encoding enzymes important for its biosynthesis and patients are responsive to CoQ10 supplementation. Early treatment allows better prognosis of the disease and therefore, early diagnosis is desirable. The complex phenotype and genotype and the frequent secondary CoQ10 deficiencies make it difficult to achieve a definitive diagnosis by direct quantification of CoQ10 . We developed a non‐radioactive methodology for the quantification of CoQ10 biosynthesis in fibroblasts that allows the identification of primary deficiencies. Fibroblasts were incubated 72 h with 28 μmol/L 2 H3 ‐mevalonate or 1.65 mmol/L 13 C6 ‐p‐hydroxybenzoate. The newly synthesized 2 H3 ‐ and 13 C6 ‐ labelled CoQ10 were analysed by high performance liquid chromatography‐tandem mass spectrometry. The mean and the reference range for 13 C6 ‐CoQ10 and 2 H3 ‐CoQ10 biosynthesis were 0.97 (0.83–1.1) and 0.13 (0.09–0.17) nmol/Unit of citrate synthase, respectively. We validated the methodology through the study of one patient with COQ2 mutations and six patients with CoQ10 deficiency secondary to other inborn errors of metabolism. Afterwards we investigated 16 patients' fibroblasts and nine showed decreased CoQ10 biosynthesis. Therefore, the next step is to study the COQ genes in order to reach a definitive diagnosis in these nine patients. In the patients with normal rates the deficiency is probably secondary. In conclusion, we have developed a non‐invasive non‐radioactive method suitable for the detection of defects in CoQ10 biosynthesis, which offers a good tool for the stratification of patients with these treatable mitochondrial diseases.